PEMANFAATAN SUMBER DAYA PERIKANAN IKAN TERI, DALAM PENINGKATAN EKONOMI MASYARAKAT DI PULO PANJANG MELALUI PRODUKSI UMKM PEYEK TERI - Hakim, Cecep Abdul; Saepudin, Saepudin; Zulfikar, Meiby; Putriauliah, Izmy; Utami, Windi (Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2023)
Panjang Island, an island in the Banten Strait archipelago which is located in Serang Regency, Banten Province has the potential for anchovy commodity. This commodity is predicted to be able to increase the income of people in Panjang Island. This study aims to study the potential of fishery resources in Pulo Panjang Village, especially anchovies. Primary data and information collected based on observation, Focus Group Discussion (FGD) with the residents of Pulo Panjang, and village officials and secondary data collection. Data were analyzed in a descriptive narrative so as to provide information about the potential for anchovy production, the average income of anchovies with absorption of human resources and fishery resources with added value of anchovy commodities. The results showed that the area of utilization of anchovy production provides better economic gains, an increase in economic value